LITERATURA INFANTIL COM TEMÁTICA DA CULTURA AFRICANA E AFRO-BRASILEIRA EM FOCO: FORMAÇÃO DE PROFESSORAS/ES E MEDIAÇÃO DA LEITURA - Silva, Sonia Dalva Pereira da (2021)
The research presented here focuses on teacher training and the work of mediating literary reading with thematic of African and Afro-Brazilian culture and actions carried out within the scope of LitERÊtura - Group of studies and research on ethnic-racial